2023
DOI: 10.1037/spq0000562
|View full text |Cite
|
Sign up to set email alerts
|

Violence directed against teachers during the COVID-19 pandemic: A social–ecological analysis of safety and well-being.

Abstract: Violence against teachers is a public health crisis that has devastating effects on school personnel well-being, health, and retention, as well as students’ educational outcomes. In collaboration with national organizations, the American Psychological Association Task Force on Violence against Educators conducted the first national survey on educator victimization that included 4,136 pre-K through 12th-grade teachers from all 50 U.S. states and Puerto Rico during the pandemic. In the current study, 43.7% of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…and life satisfaction, the findings support the assumption that teacher victimization could negatively affect their life satisfaction. However, the cross-sectional design of this study limits making definitive causal claims and indicates that this assumption, to some extent evidenced in previous research [10,34,73,106], requires validation through stronger, longitudinal designs.…”
Section: Discussionmentioning
confidence: 71%
“…and life satisfaction, the findings support the assumption that teacher victimization could negatively affect their life satisfaction. However, the cross-sectional design of this study limits making definitive causal claims and indicates that this assumption, to some extent evidenced in previous research [10,34,73,106], requires validation through stronger, longitudinal designs.…”
Section: Discussionmentioning
confidence: 71%
“…Second, the Cronbach’s α for exclusionary discipline was, while acceptable, rather low (.67). We retained the factor for theoretical reasons, in line with other studies using this construct (Reddy et al, 2023). Third, while all U.S. states are represented in this data set, the sample is not truly nationally representative, as the likelihood of responding may have been influenced by teacher safety and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Responses were then dichotomized to represent whether one of the violence items in each set occurred at least once (coded as 1) or not (coded as 0), summed based on the theoretical factor structure, and again dichotomized to represent whether respondents experienced each violence type (e.g., verbal/threatening, physical, or property) at least once (coded as 1) or not (coded as 0). This procedure was adopted to be in line with other studies examining teacher victimization (Reddy et al, 2023), as well as examining the presence or absence of victimization behaviors that occur at low frequencies (e.g., physical assault).…”
Section: Educator Victimization Scalementioning
confidence: 99%
See 1 more Smart Citation
“…This only worsened during the pandemic, wherein K-12 educators were most likely of all public sector employees to report anxiety, stress, and burnout (Mission Square Research Institute 2021). Furthermore, Reddy et al (2023) declared violence against teachers to be a "public health crisis." Using a national survey of Pre-K-to-12th grade teachers, their analysis showed that 43.7% of educators experienced at least one verbal threat, physical assault, and/or property damage, with teachers in urban communities reporting higher rates of verbal and threatening violence.…”
Section: The Rise and Consequences Of Neoliberal Reform On Teachersmentioning
confidence: 99%